# Question 3f803

Oct 7, 2017

$x = - 2$

#### Explanation:

$- 3 x - 15 = 3 x - 3$ by removing brackets in both sides.
$- 15 + 3 = 3 x + 3 x$ by bringing x terms to one side and constant the other side.
$6 x = - 12$ or $x = - \left(\frac{12}{6}\right) = - 2$

Oct 7, 2017

$x = - 2$

#### Explanation:

$\text{using the "color(blue)"distributive property}$

•color(white)(x)a(b+c)=ab+ac#

$\text{apply this concept to the brackets on both sides of the}$
$\text{equation}$

$\Rightarrow - 3 x - 15 = 3 x - 3$

$\text{collecting terms in x on the left side and numeric values}$
$\text{on the right side}$

$\text{subtract 3x from both sides}$

$- 3 x \textcolor{red}{- 3 x} - 15 = \cancel{3 x} \cancel{- 3 x} - 3$

$\Rightarrow - 6 x - 15 = - 3$

$\text{add 15 to both sides}$

$- 6 x \cancel{- 15} \cancel{+ 15} = - 3 \textcolor{red}{+ 15}$

$\Rightarrow - 6 x = 12$

$\text{divide both sides by } - 6$

$\frac{\cancel{- 6} x}{\cancel{- 6}} = \frac{12}{- 6}$

$\Rightarrow x = - 2$

$\textcolor{b l u e}{\text{As a check}}$

Substitute this value into the equation and if both sides are equal then it is the solution.

$\text{left } = \left(- 3 \times 3\right) = - 9$

$\text{right } = \left(- 3 \times 3\right) = - 9$

$\Rightarrow x = - 2 \text{ is the solution}$

Oct 7, 2017

$x = - 2$

#### Explanation:

If we look at just $- 3 \left(x + 5\right)$ for now, you have to multiply each part in the parenthesis by what it's all being multiplied by. In this case, when we multiply $x$ by $- 3$, it's $- 3 x$, then the $5$ times the same is $- 15$.

So the first side is now

$- 3 x - 15$

We do the same for the other side resulting in

$3 x - 3$

So now we have

$- 3 x - 15 = 3 x - 3$

We get all the $x$'s together by adding $3 x$ to both sides to remove it from the left and adding to the right resulting in

$- 15 = 6 x - 3$

We then add $3$ to both sides to remove it from the right and add to the left resulting in

$- 12 = 6 x$

Now we can solve for $x$ by dividing both sides by $6$, resulting in

$- 2 = x$